Nonsmooth Optimization-Based Hyperparameter-Free Neural Networks for Large-Scale Regression - Karmitsa Napsu; Taheri Sona; Joki Kaisa; Paasivirta Pauliina; Bagirov Adil M.; Mäkelä Marko M. (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
In this paper, a new nonsmooth optimization-based algorithm for solving large-scale regression problems is introduced. The regression problem is modeled as fully-connected feedforward neural networks with one hidden layer, piecewise linear activation, and the 𝐿1-loss functions. A modified version of the limited memory bundle method is applied to minimize this nonsmooth objective. In addition, a novel constructive approach for automated determination of the proper number of hidden nodes is developed. Finally, large real-world data sets are used to evaluate the proposed algorithm and to compare it with some state-of-the-art neural network algorithms for regression. The results demonstrate the superiority of the proposed algorithm as a predictive tool in most data sets used in numerical experiments.